Effective Detection of Cassava Mosaic Disease (CMD) in Cassava Plants using DRNN Technique - Yasaswini, Mulukutla Durga; Burra, Vijaya Babu (Journal of Neonatal Surgery, 2025)
Convolutional neural networks (CNNs), in particular, have been utilized to make significant progress in the field of automated leaf disease identification and diagnosis through the application of deep learning. The precision and efficiency of agricultural processes have been considerably enhanced as a result of these improvements. The previous methods of disease diagnosis relied on humanly generated features that were derived from photographs. This was the case throughout history. Consequently, these strategies typically suffered from lower resilience and flexibility as a consequence of their actions. It has been feasible to automatically extract features directly from raw images as a result of the transition to CNNs, which has made it possible to overcome these limits. The goal of this research is to investigate the use of deep learning techniques for the purpose of recognizing Cassava Mosaic Disease (CMD) in cassava plants as well as other ailments in tomato leaves. This research is being conducted within the scope of this research. Certain deep architectures that integrate residual learning and attention approaches were built in order to improve the process of extracting features from photographic images of leaves. This was done within the context of improving the process. The experimental results on the Plant Village Dataset demonstrated an impressive accuracy of 98% when it came to identifying diseases that affect tomato plants. These diseases include early blight, late blight, and leaf mold. Experiments were conducted on the dataset. In a similar vein, a deep residual convolutional neural network, also known as a DRNN, was able to achieve significant improvements in CMD detection as compared to conventional CNN implementations. The utilization of block processing and various picture enhancement techniques, such as decorrelation stretching and gamma correction, was the means by which this objective emerged. The results of this study demonstrate the potential for CNNs to act as valuable tools for farmers, providing them with the possibility to reduce crop losses and boost agricultural output. This potential was highlighted after the study was completed. In order to further improve the practical usability of deep learning technologies in plant pathology, potential future research areas may focus on scalability, model interpretability, and adaptability to a range of agricultural contexts. This is done with the intention of further boosting the utilization of these technologies in plant pathology.